Soeng Joeng Toi: opening fissures towards a platform and a bridge. Issue 3 (3rd July 2018) - Guo, Yun; Li, Xiaotian
ABSTRACT: In May of 2017, a space called Soeng Joeng Toi was established, gathering a variety of people to share and co-organise a space together. While it may be considered a relative newcomer, Soeng Joeng Toi's appearance can be seen as an inevitable breakaway from the mainstream political, economic and cultural climate of a city like Guangzhou. From its initial planning stages to its official operation, much of Soeng Joeng Toi's inspiration and methods have come from extensive exchange with independent spaces both in China and abroad, where mutual recognition of similar conditions and thinking of the commons have led these different spaces to continue developing in a sustained dialogue. This text, written from the perspective of two of Soeng Joeng Toi's "co-proprietors, " introduces the beginnings of Soeng Joeng Toi, its current operations and experiences of connecting with others as well as explores the possibilities of a shared activism involving people from different fields and geographic regions.